Distal brachii biceps tendon repair with bone tunnel - A. Santucci; A. Stancati; S. Giannetti; E. D. Pagano (National Electronic Information Consortium (NEICON), 2020)
Objective: subcutaneous rupture of the distal biceps tendon is the most common tendon injury of the elbow. Recently with the best understanding of the anatomy and the advent of new fixations many surgeons took up the use of single incision surgery, as an alternative to replace the tendon. Materials and methods: 40 male patients (average age 45,2) operated from 2006 to 2016. Results: only 3 cases had post-surgery complications: 1. a transient neurapraxia of the posterior interosseous nerve, 2. a radio-ulnar synostosis with stiffness in pronation and supination, and 3. a stiffness of the elbow in extension of approximately 5° degrees. Conclusions: the reinsertion of the distal biceps tendon with bone tunnel in anatomical site is a safe, reproducible technique that offers excellent clinical results. Patients achieve a complete recovery of the elbow range of motion, strength and endurance, with minimal risk of complications